High visceral fat with low subcutaneous fat accumulation as a determinant of atherosclerosis in patients with type 2 diabetes. Issue 1 (December 2015) - Bouchi, Ryotaro; Takeuchi, Takato; Akihisa, Momoko; Ohara, Norihiko; Nakano, Yujiro; Nishitani, Rie; Murakami, Masanori; Fukuda, Tatsuya; Fujita, Masamichi; Minami, Isao; Izumiyama, Hajime; Hashimoto, Koshi; et al.
Abstract Background Abdominal visceral obesity has been reported to be associated with cardiovascular risks than body mass index, waist circumference, and abdominal subcutaneous fat. On the other hand, there is evidence that subcutaneous fat has a beneficial role against cardio-metabolic risks such as diabetes or dyslipidemia. However, little is known regarding the association between high visceral fat with low subcutaneous fat accumulation and the risk for atherosclerosis. Methods This study was designed to elucidate whether high visceral fat with low subcutaneous fat accumulation enhances the risk for atherosclerosis in patients with type 2 diabetes. This is a cross-sectional study of 148 patients with type 2 diabetes (mean age 65 ± 12 years; 44.5 % female). Visceral fat area (VFA, cm2 ) and subcutaneous fat area (SFA, cm2 ) were assessed by abdominal computed tomography. Carotid intima media thickness (CIMT, mm) measured by ultrasonography was used for the assessment of atherosclerosis. Patients were divided into four groups: SFA < 100 cm2 and VFA < 100 cm2 [S(−)V(−)], SFA ≥ 100 cm2 and VFA < 100 cm2 [S(+)V(−)], SFA < 100 cm2 and VFA ≥ 100 cm2 [S(−)V(+)], and SFA ≥ 100 cm2 and VFA ≥ 100 cm2 [S(+)V(+)]. Linear regression analysis with a stepwise procedure was used for the statistical analyses. Results Among the patients examined, 16.3 % were S(−)V(+). Mean (95 % confidence interval) of CIMT adjusting for age and gender were 0.80 (0.69–0.91), 0.86 (0.72–1.01), 1.28 (1.11–1.44) and 0.83 (0.77–0.88) in patients with S(−)V(−), S(+)V(−), S(−)V(+) and S(+)V(+), respectively (p < 0.001). The S(−)V(+) patients exhibited significantly older than S(−)V(−) patients and those with S(+)V(+) and had a highest VFA-SFA ratio (V/S ratio) among the four groups. S(−)V(+) patients were male predominant (100 % male), and S(+)V(−) patients showed female predominance (82 % female). In multivariate linear regression analysis (Adjusted R2 = 0.549), S(−)V(+) was significantly associated with CIMT (Standardized β 0.423, p < 0.001). Notably, S(+)V(+) was inversely associated with CIMT in the multivariate model. Conclusions This study provides evidence that high visceral fat with low subcutaneous fat accumulation is an important determinant of carotid atherosclerosis and high subcutaneous fat could be protective against atherosclerosis in patients with type 2 diabetes.